School climate and adolescents’ prosocial behavior: the mediating role of perceived social support and resilience - Luo, Yun; Ma, Tangsheng; Deng, Yuting (Frontiers in Psychology, 2023)
Prosocial behavior is crucial for adolescent socialization and plays a positive role in all aspects of adolescent development. Based on ecosystem theory and self-determination theory, this study aimed to explore the relationship among school climate, perceived social support, psychological resilience, and prosocial behavior. With 1,688 high school students being sampled, we utilized the Perceived School Climate Questionnaire, the Perceived Social Support Scale, the Chinese Version of Mental Resilience Scale, and the Adolescent Prosocial Tendency Scale. The results showed that: (1) school climate, perceived social support, psychological resilience, and prosocial behavior were all positively correlated; (2) perceived social support and psychological resilience could independently mediate the relationship between school climate and prosocial behavior; these two mediating variables could develop a chain mediation effect to influence the link between school climate and prosocial behavior.